Single and composite damage mechanisms of soil polyethylene/polyvinyl chloride microplastics to the photosynthetic performance of soybean (Glycine max [L.] merr.) - Li, Haibin; Song, Fupeng; Song, Xiliang; Zhu, Kongming; Lin, Qun; Zhang, Jinliang; Ning, Guoqiang (Frontiers in Plant Science, 2023)
Adverse impacts of soil microplastics (MPs, diameter<5 mm) on vegetative growth and crop production has been widely reported, however, the single and composite damage mechanisms of polyethylene (PE) /polyvinyl chloride (PVC) microplastics (MPs) induced photosynthesis inhibition are still rarely known. In this study, two widely distributed MPs, PE and PVC, were added to soils at a dose of 7% (dry soil) to examine the single and composite effects of PE-MPs and PVC-MPs on the photosynthetic performance of soybean. Results showed PE-MPs, PVC-MPs and the combination of these two contaminants increased malondialdehyde (MDA) content by 21.8-97.9%, while decreased net photosynthesis rate (Pn) by 11.5-22.4% compared to those in non-stressed plants, PVC MPs caused the most severe oxidative stress, while MPs stress resulted in Pn reduction caused by non-stomatal restriction. The reason for this is the single and composite MPs stress resulted in a 6% to 23% reduction in soybean PSII activity RCs reaction centers, along with negative effects on soybean PSII energy uptake, capture, transport, and dissipation. The presence of K-band and L-band also represents an imbalance in the number of electrons on the donor and acceptor side of PSII and a decrease in PSII energy transfer. Similarly, PVC single stress caused greater effects on soybean chloroplast PSII than PE single stress and combined stresses.